Karakteristik Kualitatif dan Kuantitatif Induk Sapi Peranakan Onggole (PO) dan Persilangannya di Pacitan, Jawa Timur - Adisti Rastosari (Wahana Peternakan, 2017)
ABSTRACT This study aimed to determine the qualitative and quantitative characteristics of Ongole Grade Cow and its crossbreeding in Pacitan, East Java. This study used 105 cattles, which consist of 35 Ongole Grade Cattle, 35 LimPO and 35 SimPO. Ongole Grade’s coat dominated by white color (100%), coat of LimPO and SimPO dominated by light brown (5.7%) and (17.1%), brown (68.6%) and (57.1%), dark brown (25.7%) both. The muzzle color’s of Ongole Grade was (100%) black, black (48.6%) and brown (51.4%) for LimPO, black (51.4%) and brown (48.6%) for SimPO. SimPO had a white color on its head. The tail and nail color’s of Ongole Grade was (100%) black, black (48.6%) and brown (51.4%) for LimPO, black (54.3%) and brown (45.7%) for SimPO. Body sizes consisted of the heart girth, withers height, body length, hip height and head index for Ongole Grade were 160.36±9.57 cm; 122.13±5.29 cm;113.81±8.52 cm;126.31±4.77 cm; and 0.41±0.05; for LimPO were 167.27±14.33 cm;128.59±8.02 cm;124.44±8.83 cm;131.43±8.29 cm; and 0.47±0.06; for SimPO were 164.67±8.59 cm; 123.97±6.91 cm; 126.44±9.64 cm; 126.04±7.56 cm; and 0.50±0.07. From this results, it could be concluded that Ongole Grade, LimPO, and SimPO had different qualitative and quantitative characteristics which SimPO had a white color on its head. Heart girth, withers height, and hip height of LimPO were larger than SimPO and Ongole Grade whereas body length and head index of SimPO were larger than LimPO and Ongole Grade. Key Words: Cow, LimPO, Ongole grade cattle, qualitative, quantitative, SimPO.